Fat Delta 2: functorial subgroups of topological abelian groups - Dikranjan, Dikran; Lewis, Wayne; Loth, Peter; Mader, Adolf (Topology Proceedings, 2022)
In the predecessor [16] of this paper the canonical subgroup (Fat Delta) $\boldsymbol{Δ}(G)$ of a compact abelian group $G$ was studied. It is the sum of all closed disconnected subgroups of $G$ and it appeared before in the literature (see [28]) as $\operatorname{td}(G)$, defined for arbitrary topological groups and motivated by completely different considerations. We introduce and compare further functorial subgroups of general topological groups and study their relationships with $\boldsymbol{Δ}(G)$ and $\operatorname{td}(G)$.